Cost of Measles Containment in an Ambulatory Pediatric Clinic. Issue 6 (June 2015) - Wendorf, Kristen A.; Kay, Meagan; Ortega-Sanchez, Ismael R.; Munn, Meaghan; Duchin, Jeffrey
Abstract : Background: Measles is highly infectious; prompt containment of illnesses is necessary to prevent spread. In August 2013, a 13-year-old male with measles exposed patients and employees in a pediatric clinic. We studied containment costs to identify avoidable costs. Methods: Measles exposure was defined as in-person contact with or presence in the same room <2 hours after the measles patient. Costs were calculated retrospectively using published costs of measles–mumps–rubella vaccine, cost-to-charge ratios for inpatient care in urban Washington State and local emergency department charges for post-exposure immunoglobulin (IG). Personnel costs were calculated by multiplying hourly wages by time for employees who worked on the response; overhead was excluded. Results: Fifty-two patients, 60 caretakers and 10 employees were exposed. Personnel time cost 1961. Exposed patients had a mean age of 9.6 years (range: 2 months–19 years); 34 (65%) were fully vaccinated, and 18 (35%) were <12 months of age and too young to be vaccinated. Five patients (10%) were <6 months of age and required IG; 13 infants (25%) 6–11 months of age required measles–mumps–rubella vaccination. Caretakers followed up with their physicians for evidence of immunity. One employee had documented evidence of immunity; 9 required measles antibody testing or vaccination. Management of exposed persons cost 3694; overall clinic costs were 5655. Conclusion: Responding to 1 measles case cost the pediatric clinic more than 5000, despite isolating the patient promptly after examination. Documentation of employee immunity, vaccination of eligible patients and strict infection control precautions might reduce ambulatory costs associated with measles containment.